Refractory mixed peritoneal adenocarcinoma arising from the foci of external endometriosis: a clinical note - N. G. Kormosh; K. P. Laktionov; O. A. Anurova; N. S. Kerzhkovskaya (ABV-press, 2014)
The paper describes a case of mixed (clear cell and endometrioid) peritoneal adenocarcinoma developing in a patient 12 years after surgical treatment for genital endometriosis.